Experimental Study of Moment Method for Undergraduates in Electromagnetic - O. Serteller, N. F.; Ak, A. G.; Kocyigit, G.; Akinci, T. C. (Elektronika ir Elektrotechnika, 2011)
The experimental study and Moment Method with is programmed in Mathematica are presented here to facilitate introductory instruction on numerical methods for undergraduate electrical education students. The Method of Moments (MOM) is introduced at the beginning level to prepare students for subsequent advanced topics in complex matrix method and linear vector space theory. The study is carried out with parallel plate capacitor. The different capacitor (dielectric) materials are tried and coincidental program of MOM are studied. Ill. 4, bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.184